Analisis Efektivitas Implementasi Zakat Profesi dalam Meningkatkan Kesejahteraan Masyarakat di UPZ Yayasan Al-Fayyad Cikarang Utara - Hermawan, Dadang (Musyarokah: Jurnal Hukum dan Ekonomi Islam, 2023)
Participation in Professional Zakat varies between professions in the Zakat Collection Unit of Al-Fayyad Foundation Cikarang Utara, although this implementation has a positive impact on community welfare, the distribution of zakat still faces unevenness. The findings underscore the need for a more inclusive approach to ensure more equitable distribution. Challenges in public awareness and understanding related to the concept of professional zakat were also identified. Therefore, recommendations are given to improve public education about professional zakat. In addition, transparency in the management of zakat funds needs to be improved to build public trust. Nevertheless, the implementation of Professional Zakat as a whole has a positive impact on people’s welfare by meeting basic needs, such as education, health, and housing. Recommendations are given to improve the effectiveness of implementation, including collaborative efforts between zakat management institutions and communities. Professional Zakat has great potential to improve community welfare in the Zakat Collection Unit of Al-Fayyad Foundation North Cikarang. However, improvements in more equitable distribution, increased public awareness, and transparency in the management of zakat funds are needed to maximize their positive impact. This study contributes to our understanding of the role of professional zakat in creating a more equitable and sustainable economic ecosystem. keywords: zakat